THE URGENCY OF IMPROVING QUALITY USING TOTAL QUALITY MANAGEMENT (TQM) - Haeroni Haeroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores the urgency of improving quality at MA Nurul Jadid through the implementation of Total Quality Management (TQM), as the main key to achieving quality education. Using qualitative methods with a case study approach, this research found that TQM, with the support of strong leadership, active participation, and increased communication at MA Nurul Jadid, also contributed significantly in forming a culture of quality at MA Nurul Jadid